Expanding the clinical utility of glucosylsphingosine for Gaucher disease. Issue 3 (26th November 2019) - Saville, Jennifer T.; McDermott, Belinda K.; Chin, Sharon J.; Fletcher, Janice M.; Fuller, Maria
Abstract: Gaucher disease (GD) is an inherited metabolic disorder characterised by impaired catabolism of the glycosphingolipid, glucosylceramide. The deacetylated derivative, glucosylsphingosine (GluSph, lyso‐Gb1) has materialised as a biomarker for GD. Further appraisal of the clinical utility of GluSph is required in terms of its prognostic power to inform disease course and pre‐symptomatic testing. In this study, we show that plasma GluSph concentrations are significantly higher in GD patients with neuronopathic disease compared with non‐neuronopathic disease, even in the neonatal period. A neonate diagnosed at 1 day of age (homozygous for N370S) due to an affected older sibling, returned GluSph of 70 nmol/L compared with 1070‐2620 nmol/L for four neuronopathic patients diagnosed <20 days of age. Given this result shows promise for newborn screening, we developed a rapid, simple, and robust assay for GluSph in dried filter paper blood spots (DBS) and were able to detect 23 GD patients from 220 unaffected individuals. Neuronopathic GD patients also had significantly higher DBS concentrations of GluSph than their non‐neuronopathic counterparts. We went on to measure GluSph in tissue extracts prepared from chorionic villus sampling and confirmed concentrations were undetectable in unaffected tissue but elevated in GD tissue demonstrating utility in the prenatal setting. Additionally, GluSph is a pharmacodynamic biomarker, revealing a precipitous drop following initiation of enzyme replacement therapy. In conclusion, GluSph is a reliable and specific biomarker for GD and shows promise for prenatal diagnosis and DBS screening programmes.